2017
DOI: 10.18632/oncotarget.19774
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA deregulation in nonalcoholic steatohepatitis-associated liver carcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is the fastest-rising cause of cancer-related death in the United States. Recent epidemiological studies have identified nonalcoholic steatohepatitis (NASH), a progressive form of nonalcoholic fatty liver disease (NAFLD), as a major risk factor for HCC. Elucidating the underlying mechanisms associated with the development of NASH-derived HCC is critical for identifying early biomarkers for the progression of the disease and for treatment and prevention. In the present study, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 49 publications
1
37
0
1
Order By: Relevance
“…To date, most of the studies indicate a critical role of several miRNAs (miR-21, miR-29, miR-23, miR-155, miR-221, miR-222, miR-106, miR-93, miR-519) in NASH-associated carcinogenesis [ 32 ]. Strikingly, altered expression of these miRNAs have been found to be involved in major hepatocarcinogenic pathways, including the TGF- β , Wnt/ β -catenin, mitogen-activate protein kinase (MAPK), and phosphatidylinositol 3-kinases (PI3K)/AKT/mTOR that regulate proliferation and energy metabolism in the cell [ 41 ]. Importantly, several of these miRNAs target the main inhibitor of the PI3K/AKT pathway, PTEN protein, and its mutations were found in HCC patients [ 42 ].…”
Section: Molecular Mechanisms Involved In Nash-related Hccmentioning
confidence: 99%
“…To date, most of the studies indicate a critical role of several miRNAs (miR-21, miR-29, miR-23, miR-155, miR-221, miR-222, miR-106, miR-93, miR-519) in NASH-associated carcinogenesis [ 32 ]. Strikingly, altered expression of these miRNAs have been found to be involved in major hepatocarcinogenic pathways, including the TGF- β , Wnt/ β -catenin, mitogen-activate protein kinase (MAPK), and phosphatidylinositol 3-kinases (PI3K)/AKT/mTOR that regulate proliferation and energy metabolism in the cell [ 41 ]. Importantly, several of these miRNAs target the main inhibitor of the PI3K/AKT pathway, PTEN protein, and its mutations were found in HCC patients [ 42 ].…”
Section: Molecular Mechanisms Involved In Nash-related Hccmentioning
confidence: 99%
“…A further important target gene of miR-221 was shown to be the cell-cycle regulator p27(Kip1) [210,211]. Moreover, miR-221 targets are the E2F transcription factor 1 (E2F1), the phosphatase and tensin homolog (PTEN) and the cyclin-dependent kinase inhibitor 1 (CDKN1A), all belonging to critical cancer related pathways in HCC as well as other types of cancer including melanoma [212]. Bae et al showed that a miR-221 mediated suppression of HDAC6 was initiated by the JNK/c-Jun signaling pathway and by NFκBp65 nuclear translocation [213].…”
Section: Microrna-221mentioning
confidence: 99%
“…Regulation of Bcl-2, VEGF and MMP-9 by miR-221 can also induce an invasive phenotype which is further mediated by miR-221 suppressing SCD5 and thereby promoting EMT [193]. Additional miR-221 targets are c-Kit, p27Kip1/CDKN1B and CDKN1A whose downregulation in cancer induces cell proliferation [194,195,212]. MiR-210 can also influence EMT and migration via inhibition of TIMP2 [215] and activation of VMP1 [216].…”
Section: Microrna-221mentioning
confidence: 99%
“…The targets of microRNA can be multiple genes (multiplicity), or multiple microRNAs can target a single gene (cooperativity). In addition, considering their potential in carcinogenesis, microRNAs can be categorized as oncogenes or onco-microRNAs or as tumor suppressor genes [ 64 ]. miRNAs stability has been demonstrated in serum, plasma, saliva and urine.…”
Section: Epigenetics In Nafldmentioning
confidence: 99%